Nilai Budaya dalam Lirik Lagu Banjar Karya Syarifudin MS - Siti Mahmudah (Pelataran Seni, 2016)
AbstractThe value of culture is the conception of ideal or idealized images of something that is deemed valueable, life in mid and are embodied in the norms of society. The lyrics are an expression of an author who comes from inside her about something they have seen, heard and felt. The song is a song has speak Banjar. After conducting qualitative descriptive study about the Banjar song lyrics work Syarifudin MS., in particular the analysis of the music album Hindau Banua, found five categories of cultural values. Ie the value of religiosity and social mores.Keywords: banjar songs, syarifudin ms, cultural values, song lyric